1995
DOI: 10.1177/104225879501900204
|View full text |Cite
|
Sign up to set email alerts
|

Second-Career Entrepreneurs: A Multiple Case Study Analysis of Entrepreneurial Processes and Antecedent Variables

Abstract: We use open-ended interviews and focus groups to construct a composite model of activities constituting the entrepreneurial process for seven retirees from a Fortune 100 corporation who started second-career businesses. Our results show that retirees’ prior employment experience modifies the nature of entrepreneurial processes used to get into business. Technology-oriented retirees followed incremental processes, using fewer steps in the process, with an indeterminate inception in the development of required s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 27 publications
1
60
0
1
Order By: Relevance
“…Dyer asserted that children of entrepreneurs are more likely to view business ownership as being more acceptable than working for someone else. Baucus and Human (1995) studied Fortune 500 firm retirees who started their own business and found that networking, their view of departure, and prior employment experience positively affected the entrepreneurial process. Carroll and Mosakowski (1987) asserted that children with self-employed parents likely work in the family firm at an early age.…”
Section: Intentionsmentioning
confidence: 98%
“…Dyer asserted that children of entrepreneurs are more likely to view business ownership as being more acceptable than working for someone else. Baucus and Human (1995) studied Fortune 500 firm retirees who started their own business and found that networking, their view of departure, and prior employment experience positively affected the entrepreneurial process. Carroll and Mosakowski (1987) asserted that children with self-employed parents likely work in the family firm at an early age.…”
Section: Intentionsmentioning
confidence: 98%
“…En la literatura actual, se han identificado los siguientes temas para explicar las principales líneas de investigación que se han desarrollado para estudiar el fenómeno del emprendimiento del adulto mayor: Ambiente cultural y contexto emprendedor (Weber y Schaper, 2004;Kautonen,et al,2009;Pilkova, el al.,2014); Acceso financiero y otros recursos (Hart et al, 2004;Kibler et al, 2011), Barreras para emprender (Curran y Blackburn, 2001;Singh y DeNoble, 2003, Levesque y Minniti, 2006Kautonen et al, 2011;Kibler, et al, 2011, Kibler et al, 2012, Kautonen, et al, 2013, Capital humano (Singh y DeNoble, 2003;Weber y Schaper, 2004), Capital social (Baucus y Human, 1994;Singh y DeNoble, 2003;Kautonen, 2012), Historia de carrera (Baucus y Human, 1994;Kautonen et al, 2010), Emprendimiento femenino (McKay, 2001;Kautonen, 2008;Kautonen, 2012), Innovación (Botham y Graves, 2009;Colovic y Lamotte, 2012) Jubilaciones y emprendimiento (Wainright y Kibler, 2014), Motivaciones para emprender (Weber y Schaper, 2004;Kibler et. al., 2012, Kautonen et al, 2013 y finalmente Políticas Públicas (Kautonen, 2012;Halabisky 2012) A su vez, dado que cada una de las diferentes líneas de investigación descritas toman distintas perspectivas, se ha decido hacer una clasificación que aborda temas más amplios, con el fin de estudiarlos en mayor profundidad y claridad.…”
Section: Revisión De Literaturaunclassified
“…As already said, some scholars call them older entrepreneurs (Curran & Blackburn, 2001;Karoly & Zissimopoulos, 2004;Zissimopoulos & Karoly, 2007;Kerr & Armstrong-Stassen, 2011;Small, 2012;Zolin, 2015;Usman et al, 2016), while other scholars label them as grey entrepreneurs (Weber & Schaper, 2004;Botham & Graves, 2009) or senior entrepreneurs (Kautonen, 2013;Maritz, 2015). Even if some differences emerge between the above groups (Baucus & Human, 1994;Blackburn et al, 2000;Weber & Schaper, 2004), they are synonymous in this paper. Older, grey and senior entrepreneurs are considered 'someone over a certain age who begins their own small or medium-sized enterprises' (Weber & Schaper, 2004, p. 152).…”
Section: Literature Reviewmentioning
confidence: 99%